2007
DOI: 10.1111/j.1464-410x.2006.06683.x
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term results of transurethral vaporization of the prostate using plasmakinetic energy

Abstract: OBJECTIVE To assess the long‐term efficacy and the safety of plasmakinetic vaporization of prostate (PKVP, Gyrus Medical Ltd., Bucks, UK) against standard transurethral resection of the prostate (TURP) for symptomatic prostatic obstruction. PATIENTS AND METHODS Of 75 patients admitted to our clinic with symptomatic prostatic obstruction between 2001 and 2003, 40 who were randomized to undergo either TURP or PKVP, and who had returned for the follow‐up, were included in this study. All treated patients complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 22 publications
(33 reference statements)
7
44
1
3
Order By: Relevance
“…The published studies have reported significant improvement in IPSS and Q max with different follow-up durations for vaporization and vaporization-resection (including bipolar technology) in the case series (12,20,44,45) or in comparison with monopolar or bipolar TURP (19,34,43,(46)(47)(48) and our results are similar to those. In the meta-analysis studies, the PVP and B-TURP had similar results with M-TURP regarding IPSS and Q max especially in the short-term follow-up (6,14,22,31) Otsuki and co--workers reported significant improvement in IPSS between three months and one month after B-TUVP (8.8 vs. 11.1), but this matter wasn't proved about Q max (15.2 vs. 15.1mL/s) (20).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The published studies have reported significant improvement in IPSS and Q max with different follow-up durations for vaporization and vaporization-resection (including bipolar technology) in the case series (12,20,44,45) or in comparison with monopolar or bipolar TURP (19,34,43,(46)(47)(48) and our results are similar to those. In the meta-analysis studies, the PVP and B-TURP had similar results with M-TURP regarding IPSS and Q max especially in the short-term follow-up (6,14,22,31) Otsuki and co--workers reported significant improvement in IPSS between three months and one month after B-TUVP (8.8 vs. 11.1), but this matter wasn't proved about Q max (15.2 vs. 15.1mL/s) (20).…”
Section: Discussionsupporting
confidence: 88%
“…In Kaya et al research, PKVP (12%) had significantly higher re-operation rate than standard TURP (6.7%). But urethral stricture, erectile dysfunction and retrograde ejaculation were similar in both groups and no urinary incontinence or bladder neck stricture occurred (43). In Hon et al (17) and Karaman et al (47) studies, transfusion occurred only in the TURP group compared with PKVP.…”
Section: Discussionmentioning
confidence: 79%
“…[17][18][19][20] However, midterm results have been reported to be inferior compared to TURP. 7,21 In 2008, a novel bipolar device using an ergonomic, hemispherical electrode and a different energy setting was launched. 22 To date, only limited data are available for this contemporary BPV technique.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] However, in one study comparing long-term results of transurethral vaporization of the prostate using plasmakinetic energy with conventional TURP, the authors concluded that the outcomes, like the International Prostate Symptom Score (IPSS) and maximum flow rates (Qmax), of PKVP after 3 years was statistically worse than TURP (p < 0.05). 5 Most studies until now have compared the outcomes of PKR or PKVP in BPH with monopolar TURP. [1][2][3][5][6] In this study, we compared the efficacy and outcomes of PKVP with PKR in the treatment of BPH.…”
Section: Introductionmentioning
confidence: 99%
“…5 Most studies until now have compared the outcomes of PKR or PKVP in BPH with monopolar TURP. [1][2][3][5][6] In this study, we compared the efficacy and outcomes of PKVP with PKR in the treatment of BPH.…”
Section: Introductionmentioning
confidence: 99%